STRATEGI PELAYANAN BPFK SURABAYA UNTUK MENDUKUNG PENGEMBANGAN EMERGENCY VENTILATOR DALAM RANGKA MEMENUHI STANDAR K3 PERALATAN MEDIS - Ratna Wardani; Tri Dedi Setyawan (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2021)
The number of ventilators in Indonesia is considered insufficient, encouraging a number of private institutions and educational institutions to create many ventilator innovations, but there are still many ventilator prototypes that have not passed the BPFK testing. This study aims to identify the factors that cause the prototype has not passed BPFK testing and determine strategies that can be applied by BPFK Surabaya and socialize them. The method used to analyze the problem and its solution is fishbone diagram, USG, and SWOT analysis, while in evaluating the understanding of the participants in the socialization, pretest and posttest were used which were analyzed using paired t-test. The results showed that the main factor causing the problem was that the specification guidelines used were still general in nature and had not fully paid attention to the patient safety aspect, so the aggressive strategy developed was to create new specification guidelines. The results of the evaluation data analysis using the t-test showed that the value of Sig. (2-tailed) = 0.000 < 0.05, so it can be concluded that there is a significant increase in knowledge after the socialization of the new specification guidelines.